A Contextualising Islamic Education Management: Integrating Local Culture and Religious Values in the Muslim Convert Community of Outer Baduy - Hinggil Permana; Undang Ruslan Wahyudin; Ridwan Irwansyah; Iqbal Amar Muzaki; Zenab Elfzzani (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study develops a culturally grounded Islamic education management model tailored for the Muslim convert community of the Outer Baduy Tribe in Banten Province, Indonesia. The model is implemented through the Paket School program, which serves as an alternative pathway to formal education. By integrating Islamic values with local cultural principles such as honesty, cooperation, simplicity, and collective responsibility, the model ensures that Islamic teachings are accepted without causing cultural resistance. This research uses a qualitative case study approach, involving 35 key participants, including traditional leaders, Paket School educators, and community members from three main villages. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analysed using thematic analysis. The findings reveal that the educational management system in the Outer Baduy community is flexible, participatory, and culturally relevant. The alignment of Islamic education with local customs through adaptive scheduling, the use of the local dialect in instruction, and community participation has proven effective in promoting both educational and behavioural outcomes. The success of the Paket School program in fostering Islamic identity and strengthening cultural values highlights the importance of integrating local wisdom into educational management. However, the study's focus on a single community and the short observation period limit the ability to generalise the findings. Future research should explore similar models in other indigenous communities, using longitudinal or mixed-methods approaches to gain deeper insights into the long-term effects of culturally grounded educational management. This research contributes to the development of inclusive, adaptive, and sustainable educational practices for marginalised and indigenous communities.